2022
DOI: 10.1038/s41598-022-23321-7
|View full text |Cite
|
Sign up to set email alerts
|

Manatee calf call contour and acoustic structure varies by species and body size

Abstract: Vocal activity and signal characteristics of mammals are driven by several factors that result in both stability and plasticity over multiple time scales. All three extant species of manatee communicate with several calls that are especially important for maintaining contact between cows and calves. Determining if calf calls differ across manatee species will provide insights into the evolution of species-specific acoustic communication traits. We investigated the interspecific differences in the vocalizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…There are several possible explanations for the differences in call types we observed. For instance, previous studies by Brady et al (2021, 2022) suggest that the hill‐shaped call is a stereotypical call type produced by younger manatee calves. It's possible that one of the calves in our study only produced high squeaks while the older calf only produced squeaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several possible explanations for the differences in call types we observed. For instance, previous studies by Brady et al (2021, 2022) suggest that the hill‐shaped call is a stereotypical call type produced by younger manatee calves. It's possible that one of the calves in our study only produced high squeaks while the older calf only produced squeaks.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, manatees could alter the structure of vocalizations in anticipation of feeding events. Additionally, the calls of Florida and Antillean manatee calves are distinctly structured and become more like adult calls over time suggesting the vocal behavior of calves is flexible (Brady et al, 2022).…”
mentioning
confidence: 99%
“…( 1234567890 www.nature.com/scientificreports/ higher than the calls reported from Puerto Rico. High squeaks are produced by both Antillean and Florida manatee calves, while adults produce squeaks 37,45,46 . This study indicates differences in acoustic parameters between adults (squeaks) and calves (high squeaks) between geographic locations.…”
Section: Discussionmentioning
confidence: 99%
“…Squeaks, high squeaks and squeals are more commonly observed in reports of Florida manatee communication 37 , 40 , 45 . Recent studies found the high squeak is a stereotypical call produced by both Florida 45 , 46 and Antillean calves 46 . As the animal grows, the hill-shaped contour of the high squeak appears to flatten and become a more linear call 46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation